Aplicações forenses do Probe Electrospray Ionization Mass Spectrometry com filme de polipirrol - Bernardo, Ricardo Alves (2017)
In this study, we developed a solid phase microextraction (SPME) method to extract Cocaine, Lisergic Acid Diethylamide (LSD), Methamphetamine (MA) and [3,4 – Methylenedioxymethamphetamine] (MDMA), which allowed the direct analysis by MS in a Probe Electrospray Ionization Mass Spectrometry (PESI-MS). PPy fibers were deposited on a platinum wire. These fibers were subjected to drug extraction from biological fluids employing SPME principles. After that, the coated platinum wire was positioned in front of the MS and then a high voltage (HV) was applied on it. At the same time, methanol (formic acid 0,1%) was used to assist the analytes desorption, ionization, and detection. Parameters as number of cycles in electrochemical process, pH, temperature of extraction and matrix effect were evaluated. The coated PESI-MS method presented linearity in a concentration range from the limit of quantification (LOQ) to 500 ng.L-1 (ppb). The LOQ values ranged from 2 ng.L-1 to 10 ng.L-1. The interday precision presented values from 0.8 to 9.6% with accuracy ranging from -0.6 to 13.7%. The intraday precision obtained values varied from 1.7 to 10.8% with accuracy ranging from -2.4 to 14.0%. The absolute recovery was also evaluated and presented values from 97.6 to 114.0%. The proposed method is a promising alternative to fast sampling and analysis for avoiding laborious process, and for showing precision and accuracy according to the values proposed by ANVISA.